Melting regime of the anionic phospholipid DMPG new lamellar phase and porous bilayer model - Spinozzi, Francesco (Langmuir : the ACS journal of surfaces and colloids, 2010)
Aqueous dispersions of the anionic phospholipid dimyristoyl phosphatidylglycerol (DMPG) at pH above the apparent pK of DMPG and concentrations in the interval 70-300 mM have been investigated by small (SAXS) and wide-angle X-ray scattering, differential scanning calorimetry, and polarized optical microscopy. The order-disorder transition of the hydrocarbon chains occurs along an interval of about 10 degrees C (between T(m)(on) approximately 20 degrees C and T(m)(off) approximately 30 degrees C). Such melting regime was previously characterized at lower concentrations, up to 70 mM DMPG, when sample transparency was correlated with the presence of pores across the bilayer. At higher concentrations considered here, the melting regime persists but is not transparent. Defined SAXS peaks appear and a new lamellar phase L(p) with pores is proposed to exist above 70 mM DMPG, starting at approximately 23 degrees C (approximately 3 degrees C above T(m)(on)) and losing correlation after T(m)(off). A new model for describing the X-ray scattering of bilayers with pores, presented here, is able to explain the broad band attributed to in-plane correlation between pores. The majority of cell membranes have a net negative charge, and the opening of pores across the membrane tuned by ionic strength, temperature, and lipid composition is likely to have biological relevance